Pandangan Mustafa Mahmud Terhadap Hadis Syafa’at - habib habib bullah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2018)
Abstract: The renewal discourse about Islamic opinion is always interesting to discuss. Many Moslem scholars give critical opinion about the reaction of knowing and understanding about Islam especially about as-sunah as a law Islamic base. The reaction is there are many people receive and there are many people refuse the exsistent of as-sunnah as a law Islamic base. One of person who refuse as-sunnah as a law Islamic base is Mustafa Mahmud. The controversial opinion becomes serious discussion both in seminar and scientific written. According to Mustofa Mahmud, all hadits are doubt not only in the exsistent but also in syafa’at hadits. They are all false although they are written by Al-Bukhari. Syafa’at hadits is often connected with refusal hadits community (refusal as-sunnah) that is placed in Mesir. This research uses analysis descriptive method that contains critical analysis inside to Mustofa Mahmud’s facing in syafa’at hadits. This research produces a critical opinion and measurement to Mustafa Mahmud’s facing about syafaat hadits.